Nomenclature and description of Electro-Luminescence (EL) observations: cell cracks and other observations - Jaeckel Bengt; Pander Matthias; Schenk Paul; Linsenmeyer Aswin; Kirch Jochen (EPJ Photovoltaics)
Crystalline silicon solar cells were, are and will continue to dominate the Photovoltaic PV module market. In the past decade, significant efforts have been made to better understand and characterize observations using Electro-Luminescence (EL) to investigate the appearance of c-Si solar cells. While standards have been developed, a clear definition of the nomenclature for observations in EL images is still missing. Within the project PV-Riss, a group comprising manufacturers, advisory experts and research facilities worked on an overview of various observations found in the literature (typically of Al-BSF and PERC cells). The individual observations were categorized into four main categories, namely: 1) single cracks, 2) multi-cracks, 3) anomalies in the electrical circuit and all others into 4) miscellaneous. Each category includes several subcategories to include most relevant observations within EL images. These categories can be applied to all existing and new cell types and are independent on the size (ranging from “old” 4” to new M/G12), shape (full, half, third, x-cut), material (mono, multi), or cell technology (AlBSF, PERC, TOPCON, HJT, IBC, Perovskite on Si), as well as of the PV module design (size, glass/backsheet, glass/glass, internal wiring of the electric circuit). Along with a detailed description of observations in EL images, several important definitions are provided that are essential for general understanding, nomenclature, and the mapping of observations to ensure clear and comprehensive communication and reporting. Following the definition of most relevant observations, key observations will be discussed within a classification proposal. This classification proposal aims to facilitate future discussions and to assess EL observations, combining the risk of power loss that exceeds warranty with the probability of potential electrical safety risk.